Orange juice decreases low-density lipoprotein cholesterol in hypercholesterolemic subjects and improves lipid transfer to high-density lipoprotein in normal and hypercholesterolemic subjects - Cesar, Thais B. [UNESP]; Aptekmann, Nancy P.; Araujo, Milena P. [UNESP]; Vinagre, Carmen C.; Maranhao, Raul C. (Pergamon-Elsevier B.V. Ltd, 2010)
Orange juice (OJ) is regularly consumed worldwide, but its effects on plasma lipids have rarely been explored. This study hypothesized that consumption of OJ concentrate would improve lipid levels and lipid metabolism, which are important in high-density lipoprotein (HDL) function in normolipidemic (NC) and hypercholesterolemic (HCH) subjects. Fourteen HCH and 31 NC adults consumed 750 mL/day OJ concentrate (1:6 OJ/water) for 60 days. Eight control subjects did not consume OJ for 60 days. Plasma was collected before and on the last clay for biochemical analysis and an in vitro as
Keywords: Cholesterol; Orange juice; Human lipoproteins; Nanoparticles; Lipid transfer